Mathematical modeling of thin layer drying using open sun and shade of Vernonia amygdalina leaves - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (Elsevier, 2018)
The drying behavior of Vernonia amygdalina leaves was investigated using open sun and shade drying. The effective diffusivity coefficients for both methods were evaluated. Eight drying kinetics models were fitted to the experimental data obtained from the two drying methods; the goodness of fit was evaluated using three statistical tools, and the best model was selected. The Midilli and Kucuk model, which gave higher values of the coefficient of determination and lower values of the reduced chi-square and root mean square error was considered the best for predicting the drying behavior of open sun-dried and shade-dried V. amygdalina leaves with values of R of 0.99951 and 0.99981, RMSE of 0.00243 and 0.00253 and reduced chi-square of 0.000511 and 0.000428, respectively. The values of the effective diffusivity coefficients for open sun and shade drying were 26.58 × 10−10 m2/s and 52.77 × 10−11 m2/s, respectively. Furthermore, open sun drying resulted in severe deformity of the leaf morphology which may lead to degradation of the phytochemicals. Thus, shade drying was the better way of drying V. amygdalina leaves to preserve the nutrients compared to open sun drying.